2007
DOI: 10.1897/06-458r.1
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of dioxins in contaminated soils with the CALUX and CAFLUX bioassays, an immunoassay, and gas chromatography/high‐resolution mass spectrometry

Abstract: The chemically activated luciferase expression assay, the chemically activated fluorescence expression assay, and the enzyme-linked immunosorbent assay (ELISA) are all bioanalytical methods that have been used for the detection and quantification of polychlorinated dibenzo-pdioxins and polychlorinated dibenzofurans (PCDD/Fs). However, no comparisons of the results obtained by these three methods have been published analyzing identical replicates of purified sample extracts. Therefore, we have evaluated the per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Studies in other areas have successfully showed that EIA analysis can potentially be used as a complementary screening tool to avoid some of the costs involved and the time required analyzing samples using HRGC/HRMS. Studies examining the ability of EIA analysis to screen for PCDD/F in soils, sediments, and fish are especially promising (Nording et al 2007;Tsutsumi et al 2008;Emon et al 2008). Our EIA results indicate that all of the soil samples contained PCDD/F concentrations lower than the regional screening value of 19.0 g EIA-TEQ/g, which was determined in a previous study (Li et al 2009).…”
Section: Resultssupporting
confidence: 64%
“…Studies in other areas have successfully showed that EIA analysis can potentially be used as a complementary screening tool to avoid some of the costs involved and the time required analyzing samples using HRGC/HRMS. Studies examining the ability of EIA analysis to screen for PCDD/F in soils, sediments, and fish are especially promising (Nording et al 2007;Tsutsumi et al 2008;Emon et al 2008). Our EIA results indicate that all of the soil samples contained PCDD/F concentrations lower than the regional screening value of 19.0 g EIA-TEQ/g, which was determined in a previous study (Li et al 2009).…”
Section: Resultssupporting
confidence: 64%
“…The conventional method, high-resolution chromatography/mass spectrometry, is time-consuming, costly, and requires large sample volumes. A previous comparison of results obtained using the two assays revealed few differences (51). For our assessments, involving limited volumes of saliva, the CALUX bioassay was a useful tool for evaluating dioxins.…”
Section: Discussionmentioning
confidence: 67%
“…These assays have been shown to produce similar results, with the advantage that the EGFP provides a nondestructive readout (Nagy et al 2002; Nording et al 2007; Peters et al 2006). We calculated AhR agonist activity values, presented as picograms TCDD equivalents (eq) per milliliter, by interpolation from TCDD standard curves.…”
Section: Resultsmentioning
confidence: 97%